2005
DOI: 10.1159/000086997
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Applications of Endoscopic Ultrasound to Oncology

Abstract: Endoscopic ultrasound (EUS) is a useful imaging modality in patients with certain gastrointestinal malignancies as well as lung cancer. In many cases, EUS has been shown to have superior staging accuracy compared with other imaging techniques such as computed tomography, magnetic resonance imaging and positron emission tomography. This article will review the role of EUS in diagnosing and staging esophageal, rectal, pancreatic and lung cancers as well as subepithelial lesions. Newer therapeutic applications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 146 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…These complications have led to the development of an anterior approach under the guidance of transcutaneous ultrasound, computed tomography or EUS ( Figure 2) [18,[30][31][32]60] . EUS allows for real-time imaging of the celiac space for CPB and CPN as well as fine needle aspiration (FNA) for diagnostic purposes and tumor staging [10,[34][35][36][37][38]71] . EUS-guided fine needle injection has been used even in patients with enternal self-expandable stents [39] .…”
Section: And Neurolysismentioning
confidence: 99%
“…These complications have led to the development of an anterior approach under the guidance of transcutaneous ultrasound, computed tomography or EUS ( Figure 2) [18,[30][31][32]60] . EUS allows for real-time imaging of the celiac space for CPB and CPN as well as fine needle aspiration (FNA) for diagnostic purposes and tumor staging [10,[34][35][36][37][38]71] . EUS-guided fine needle injection has been used even in patients with enternal self-expandable stents [39] .…”
Section: And Neurolysismentioning
confidence: 99%
“…5,6,[15][16][17][18] Compared to T1N0 tumors, creased depth of invasion. [19][20][21] Together, this makes the controversial treatment algorithm of cT2 even more complicated. Abbreviations: CI, confidence interval; HR, hazard ratio.…”
mentioning
confidence: 99%
“…In addition, it is unknown why the hospital location had an impact on stage discrepancy. Although several studies have demonstrated the superiority of computed tomography, positron emission tomography, and magnetic resonance imaging over EUS to diagnosis distant metastatic disease, EUS is more accurate in identifying local regional disease, with a sensitivity of 80% to 90% and specificity greater than 90%6,[19][20][21][28][29][30] The addition of fine-needle aspiration of equivocal clinical lymph nodes on EUS increases the sensitivity and T A B L E 3 Univariate and multivariable analysis for the impact of T-and N-classification discrepancy on overall survival…”
mentioning
confidence: 99%
“…Patients with any nodal involvement (N + ) or advance tumors (T2-T4a) (Figure 1) need preoperative neoadjuvant chemoradiotherapy, whereas T1 patients with no nodal metastasis can benefit from endoscopic (Tis, T1a N0) or surgical resection (T1bN0)[10-12]. When different staging methods were compared, CT, MRI and PET-scan showed themselves to be better than EUS in evaluating distant metastasis (M), however EUS proved superiority in the detection of tumor stage (T) and lymph nodes (N)[13-16]. One method does not have to exclude the other.…”
Section: Esophageal Cancermentioning
confidence: 99%